Review of Thomas McCabe (ed.) 2021, Descent and Logic in Biosystematics. Juneau: Perseverant Publishing - Giuliani, Alessandro (Organisms. Journal of Biological Sciences, 2021)
Review of: Thomas McCabe (ed.) 2021, Descent and Logic in Biosystematics. Juneaus: Pereseverant Publishing